Desain Dan Analisa Barrel, Screw Serta Produk Mesin Injection Molding Dengan Menggunakan Simulasi - Kiswantoro, Beny, Joko Sedyono, ST, M.Eng, Ph.D, Muh. Alfatih Hendrawan, ST, MT (2017)
The purpose of this study was to create a design, analysis, and simulation of the power screw and barrel Injection molding machine with Solidworks 2010 and know the value of mobile products in simulation using Moldflow Plastic Adviser 2014 software. In addition, to determine the value of the yield strength and the maximum value of von mises of the material used in the screw and barrel to obtain the Safety Factor to determine the safety of the materials used. In the process of design, analysis, and simulation of the investigated on the screw, barrel and plastic products. The material used in the screw is AISI 1020 carbon steel, the material used in the barrel are AISI 316 stainless steel, while the material used for mobile products is Acrylonitrile Butadiene Styrene (ABS). Software used in the present study using Solidworks 2010 and Moldflow Plastic Adviser, 2014. The results of the analysis and simulation of the screw, barrel and injection molding machinery products showed that the value of the yield strength of the screw is (351571000 N / mm²), while the value of maximum von mises is 124439192 N / mm², Safety Factor screw is 2.83. So that the screw is declared safe. In addition the value of the yield strength of the barrel is (172,368,923.3 N / mm²), while the value of maximum von mises are 76,516,120 N / mm², Safety Factor barrel is 2.25. So that the material used is declared safe. And for the parameters on its own products produced ideal pressure of 65.03 MPa and ideal temperature of 221.8 ° C. Keywords : Yield Strength, Von Mises, Safety Factor.